Limit calculation technology using linear substitutions - Abdusalom Khakimov (Genius Journals, 2024)
The article discusses the issues of simplifying the calculation of some non-standard sequences and limits of functions using linear substitutions, lemmas, and theorems.
Keywords: Software and didactic complex; limit calculation methods; calculating limits using lemmas